Color - tunable photoluminescence and energy transfer of (Tb1-xMnx)3Al2(Al1-xSix)3O12:Ce3+ solid solutions for white light emitting diodes; RSC Advances; Vol. 8, iss. 63 - Lang Tianchun; Han Tao; Zhao Cong; Cao Shixiu; Fang Shuangqiang; Li Shuai; Korepanov V. I. Vladimir Ivanovich; Yakovlev A. N. Aleksey Nikolaevich (2018, 2018)
Title screen